The acquisition of WH-questions: A simple case in Indonesian children - Iwan Fauzi (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2012)
In the first stage of language acquisition, children do not give any question word markers to their utterances. The questions without an interrogative word can be thought of yes/no– nucleus, where the yes/no marker is expressed as rising intonation. The most common wh question forms in children are some version of What’s that? and Where Nounphrase (go)? and What Nounphrase doing? This study discusses the typical forms of WH-question construction in Bahasa Indonesia acquired by Indonesian children in the early stage of their language development.